15-16 yaş İmam-Hatip Lisesi ergenlerinde sorumluluk ve dini sorumluluk seviyelerinin incelenmesi - Kaya, Feyza (My University, 2000)
15 - 16 Yaş İmam - Hatip Lisesi Ergenlerinde Sorumluluk ve Dini Sorumluluk Seviyelerinin İncelenmesi konulu tez, 15 -16 yaş ergenlik döneminin genel özelliklerini, kardeş sırasına göre özellikleri, ergende sorumluluk ve dini sorumluluk bölümü altında ; sorumluluğun tanımını, kay nağını , sorumluluk şuurunun kazanılmasına etki eden faktörleri, sorumluluk şuurunun toplum açısından önemini, ergenlerde sorumluluğun gelişimini eğitim ve öğretim sistemimizin sorumluluk açısından değerlendirilmesini, dini sorumluluğun tanımını, dinen sorumlu olanın kim olduğunu, dini sorumluluk yaşının kaç yaş olduğunu, dinen sorumlu olanların sorumluluklarını, dini sorumluluğun kaynağını, dini sorumluluk şuurunun önemini, ergenlerde dini sorumluluğun gelişimini, dini eğitim ve öğretimde dini sorumluluğu ve İ.H.Liselerinin sorumluluk ve dinin sorumluluk açısından değerlendirilmesini ve ilk kez geliştirilen Sorumluluk ve Dini Sorumluluk ölçeklerinin nasıl hazırlandığını, 15 - 16 yaş İ.H.Liselerindeki ergenlere uygulanılmasını ve elde edilen sonuçları içermektedir. Her iki ölçeye verilen cevaplar ile cinsiyet, doğum yeri, anne - baba mesleği, anne - baba öğrenim durumu, ailenin maddi durumu, kardeş sayısı ve doğum sırası değişkenleri arasındaki ilişki incelenmiştir. Her iki ölçeğin sonuçlarına göre; araştırmaya katılan bütün ergenlerde sorumluluk gelişimi ile dinin sorumluluk gelişiminin birbirine paralel olarak geliştiği, cinsiyet faktörünün sorumluluk ve dini sorumluluk gelişiminde farklılık oluşturmadığı, ergenlerin doğum yerleri ve annelerinin öğrenim durumu ile dinin sorumluluk gelişimleri arasında anlamlı bir ilişki olduğu diğer değişkenler ile sorumluluk ve dini sorumluluk gelişimine arasında anlamlı bir ilişki olmadığı ortaya çıkmıştır. Sorumluluk ve dini sorumluluk gelişimi için eğitimde uygulanılması gereken bir takım öneriler sunulmuştur. Ek'te geliştirilen Sorumluluk ve Dini Sorumluluk ölçekleri verilmiştir.

My thesis is about Examination of the Level of the Religious Responsibility and Responsibility in the Adolescence at the age of 15 - 16 in Religious High School. My thesis contains the general characteristics of the period of adolescence between the ages of 15 - 16; according to the sequence of their brothers and sisters and the explanation, source, and the factors that influence the acquisition of the consciousness of the responsibility under the point of responsibility and religious responsibility in adolescence. And also the importance of the consciousness of responsibility on the point of view of the society. Besides that the development of the responsibility in the adolescence, evaluation of the educational and training system on the point of view of responsibility, description of religious responsibility, who is responsible in the religion and what is the age of being responsible in the religion and responsibilities of who are responsible in the religion. The source of religious responsibility, the importance of consciousness of the religious responsibility, development of religious responsibility in the adolescence, the religious responsibility in religious education and training and evaluation Religious High Schools on the point of view religious responsibility and responsibility. The results and the way of preparation of the measurements of responsibility and religious responsibility which were improved and practiced on the adolescence for the first time. Both the given answers to both measurements and sex, place of birth, career of parents, studying level of parents, financial condition of the family, number of sisters and brothers, and the relations between the parameters during the birth were investigated. According to the results of the two measurements; both responsibility and religious responsibility were improved parallel in all the adolescence who joined to the investigation, the sex factor didn't show any differences in responsibility and religious responsibility, there was a meaningful relation between the places of birth and level of education and the growth of the religious responsibility of the parents and there wasn't a meaningful relation between the responsibility and religious responsibility and the other parameters. The necessary suggestions which should be practiced in education to help the growth of responsibility and religious responsibility were presented. The improved measurements of responsibility and religious responsibility were enclosed.
Keywords: Din eğitimi; Eğitim; İmam hatip liseleri; Orta öğretim